Mine mechanization and automation : proceedings of the Second International Symposium on Mine Mechanization and Automation, Lulea, Sweden, 7-10 June 1993 - Almgren, Gunnar; Kumar, Uday; Vagenas, Nick (Balkema, 1993)
These proceedings include papers on recent development in mine mechanization and automation, representing about 30 countries worldwide, covering wide mineral areas such as metal mines, industrial minerals and coal.